Phytochemicals and bioactivities of Syzygium filiforme var. filiforme - Mohd Hafiz Ahmad; Norhazana Nor Izan; Nor Hadiani Ismail; Humera Naz (Penerbit Universiti Kebangsaan Malaysia, 2021)
Syzygium filiforme var. filiforme is a plant variety from dicotyledonous plant family (Myrtaceae). Phytochemical studies on S. filiforme var. filiforme stem bark have successfully isolated and characterized arjunolic acid (1), alphitolic acid (2), betulinic acid (3), ursolic acid (4), ursolic acid 3-methyl ester (5), β-sitosterol (6) and stigmasterol (7). The inhibitory activities against free radical, starch, and bacteria for major compounds were tested by using DPPH, α-glucosidase and minimum inhibitory and bacterial concentration assays, respectively. No promising antioxidant activity was shown on tested samples except methanolic crude extract. For antidiabetic activity, methanolic and dichloromethane crude extracts displayed potent activity compared to 1-deoxynojirimycin. Minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) assays for antibacterial activity were evaluated on Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. All crude extracts and major compounds displayed weak and no promising activities for MIC method, respectively. Meanwhile, for MBC method, hexane crude extract and compound 1 showed inhibition against B. subtilis.